Impact of the Publication of Appropriate Use Criteria on Utilization Rates of Myocardial Perfusion Imaging Studies in Ontario, Canada: A Population‐Based Study - Roifman, Idan (J Am Heart Assoc, 2017)
BACKGROUND: Concern regarding overutilization of cardiac imaging has led to the development of appropriate use criteria (AUC). Myocardial perfusion imaging (MPI) is one of the most commonly used cardiac imaging modalities worldwide. Despite multiple iterations of AUC, there is currently no evidence regarding their real‐world impact on population‐based utilization rates of MPI. Our goal was to assess the impact of the AUC on rates of MPI in Ontario, Canada. We hypothesized that publication of the AUC would be associated with a significant reduction in MPI rates. METHODS AND RESULTS: We conducted a retrospective cohort study of the adult population of Ontario from January 1, 2000, to December 31, 2015. Age‐ and sex‐standardized rates were compared from 4 different periods intersected by 3 published iterations of the AUC. Overall, 3 072 611 MPI scans were performed in Ontario during our study period. The mean monthly rate increased from 14.1/10 000 in the period from January 2000 to October 2005 to 18.2/10 000 between November 2005 and June 2009. After this point in time, there was a reduction in rates, falling to a mean monthly rate of 17.1/10 000 between March 2014 and December 2015. Time series analysis revealed that publication of the 2009 AUC was associated with a significant reduction in MPI rates (P<0.001). This translated into ≈88 849 fewer MPI scans at a cost savings of ≈72 million Canadian dollars. CONCLUSIONS: Our results reflect a potential real‐world impact of the 2009 MPI AUC by demonstrating evidence of a significant effect on population‐based rates of MPI.